Shifted balance of dorsal versus ventral striatal communication with frontal reward and regulatory regions in cannabis‐dependent males - Zhou, Feng; Zimmermann, Kaeli; Xin, Fei; Scheele, Dirk; Dau, Wolfgang; Banger, Markus; Weber, Bernd; Hurlemann, René; Kendrick, Keith M.; Becker, Benjamin (Human brain mapping, 2018)
The transition from voluntary to addictive behavior is characterized by a loss of regulatory control in favor of reward driven behavior. Animal models indicate that this process is neurally underpinned by a shift in ventral–dorsal striatal control of behavior; however, this shift has not been directly examined in humans. The present resting state functional magnetic resonance imaging (fMRI) study employed a two‐step approach to: (a) precisely map striatal alterations using a novel, data‐driven network classification strategy combining intrinsic connectivity contrast with multivoxel pattern analysis and, (b) to determine whether a ventral to dorsal striatal shift in connectivity with reward and regulatory control regions can be observed in abstinent (28 days) male cannabis‐dependent individuals ( n = 24) relative to matched controls ( n = 28). Network classification revealed that the groups can be reliably discriminated by global connectivity profiles of two striatal regions that mapped onto the ventral (nucleus accumbens) and dorsal striatum (caudate). Subsequent functional connectivity analysis demonstrated a relative shift between ventral and dorsal striatal communication with fronto‐limbic regions that have been consistently involved in reward processing (rostral anterior cingulate cortex [ACC]) and executive/regulatory functions (dorsomedial prefrontal cortex [PFC]). Specifically, in the cannabis‐dependent subjects, connectivity between the ventral striatum with the rostral ACC increased, whereas both striatal regions were uncoupled from the regulatory dorsomedial PFC. Together, these findings suggest a shift in the balance between dorsal and ventral striatal control in cannabis dependence. Similar changes have been observed in animal models and may promote the loss of control central to addictive behavior.